EFEKTIVITAS KONSELING NARATIF DALAM MENINGKATKAN PENERIMAAN DIRI PADA INDIVIDU LANJUT USIA DI PANTI WREDHA - Mahardika, Nur; Sari, Siwi Vilia Intan (Universitas Islam Indonesia, 2025)
ABSTRACT: Self-acceptance is a key aspect of psychological well-being, reflecting an individual’s ability to positively embrace personal strengths and weaknesses. Elderly residents in nursing homes often face psychological challenges that can reduce self-acceptance, such as loss of social roles, declining health, and limited interactions. This study aimed to examine the effectiveness of narrative counseling in improving self-acceptance among elderly individuals in a nursing home. The research employed a quasi-experimental design with a pretest-posttest control group model. Participants consisted of 20 elderly individuals (10 experimental group, 10 control group) selected purposively. The analysis revealed a significant increase in self-acceptance in the experimental group compared to the control group. These findings suggest that narrative counseling is an effective psychological intervention to help elderly individuals develop a positive view of themselves, contributing to improved quality of life. Key words: Elderly, narrative counseling, self-acceptance. ABSTRAK: Penerimaan diri merupakan salah satu aspek penting dari kesejahteraan psikologis yang mencerminkan kemampuan individu untuk menerima kelebihan dan kekurangan dirinya secara positif. Individu lanjut usia di panti wredha sering menghadapi tantangan psikologis yang dapat menurunkan tingkat penerimaan diri, seperti kehilangan peran sosial, kesehatan yang menurun, dan keterbatasan interaksi. Penelitian ini bertujuan menguji efektivitas konseling naratif dalam meningkatkan penerimaan diri pada lansia di panti wredha. Desain penelitian menggunakan kuasi-eksperimen dengan model pretest-posttest control group. Subjek berjumlah 20 lansia (10 kelompok eksperimen, 10 kelompok kontrol) yang dipilih secara purposif. Hasil analisis menunjukkan peningkatan signifikan penerimaan diri pada kelompok eksperimen dibandingkan kelompok kontrol. Temuan ini mengindikasikan bahwa konseling naratif efektif digunakan sebagai intervensi psikologis untuk membantu lansia mengembangkan pandangan positif terhadap diri mereka, yang berdampak pada peningkatan kualitas hidup. Kata kunci: Konseling naratif, lansia, penerimaan diri.